Spurred to Upgrade: A Review of Triggers and Consequences of Industrial Upgrading in the Global Value Chain Literature. (October 2017) - Pipkin, Seth; Fuentes, Alberto
Highlights: First-ever systematic review of upgrading causes and consequences in global value chains (GVC) case literature in developing countries. Finds that buyers are not as prevalent in initiating upgrading as state policies. Finds that nearly all upgrades are prompted by "vulnerability shocks" that render firms' status quo impossible. Identifies extreme upgrading outcomes ("treadmilling, " "leaps forward"), their main characteristics, and sources in the local environment. Proposes an 'induced search' framework to evaluate causes and consequences of industrial upgrading in developing-country suppliers. Summary: The Global Value Chains (GVC) literature intervenes in today's challenging development context by focusing on the means by which developing-country industries can 'upgrade' their market positions and outcomes for workers. Yet while this literature has produced hundreds of rich empirical case studies, there has to date been no attempt to systematically analyze this case literature for lessons regarding the antecedents and consequences of the key outcome of upgrading. This paper undertakes a systematic analysis of a representative sample of 45 case studies of primary product and light manufacturing industries in developing countries. These studies were coded for factors involved in initiating and sustaining upgrading processes, the results of upgrading, and the role of local institutions in these processes. We find that contrary to the major assumptions of the literature, advanced-country buyers are not the main force in the initiation of industrial upgrading. Rather, in most cases, developing-country firms initiate upgrades when pushed by "shocks" of market vulnerability, usually produced by state policies, that force them to seek to change their status quo operations. Once initiated, upgrading processes can produce a wide spectrum of results—from little to no advancement in market position ('treadmilling') to vaulting to the forefront of a global industry ('leaps forward')—on the basis of the sources of learning present in the local institutional environment, such as state agencies and business associations. We also identify conditions under which state participation in upgrading processes can lead to increased local institutional capacity. Together, these findings suggest a framework for upgrading that we refer to as an 'induced search' model. This model has important implications for future research on the dynamics of industrial upgrading in developing countries, techniques of state intervention, and processes of mutually supportive learning between actors in the public and private sector.